Power-efficient Mode of the Electrolytic Fluorine Production Process Control; Procedia Chemistry; Vol. 11 : 1st International Symposium on Inorganic Fluorides: Chemistry and Technology, ISIF 2014, Tomsk, Russia - Gladyr E. M.; Liventsova N. V. Nina Vladimirovna; Liventsov S. N. Sergey Nikolaevich; Egorova O. V. Olga Viktorovna (2014, 2014)
Title screen